Pricing of a container services in the shipping line with special reference to integrated forwarding and Shipping Sdn. Bhd Port Klang / Adilah Shuib - Shuib, Adilah (1992)
Maritime transport plays an important role in the international trade. It is the aim of this study to identify those problems related to pricing of container services and to give recommendations to minimise the problems so that the industry may be well developed. The main problem in the shipping industry is the high freight charges, arising from great competition, unstable market situation and other factors affecting ocean freight rates. These factors are discussed in detail in this exercise